An econometric analysis of West-German coffee imports - Gerd Ronning (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1989)
The paper analyses German import sof green coffee using both descriptive statistical and econometric tools. As determinants of import demand we consider not only prices and income but also the structure of the German market of roasted coffee and two institutional arrangements which had considerable influence on German coffee imports. One is the International Coffee Agreement and the other is the Lome Convention. West-German coffee imports which have grown steadily over the last three decades play an important role in world coffee demand. However, the demand structure differs from that of many other countries. In Germany high qualities have a much larger share of imports although the distribution of shares of export countries has changed, especially during the last ten years. A descriptive statistical analysis shows that this change has affected the shares of the four broad categories of coffee (Columbian Mild, Other Milds, Unwashed Arabica, Robusta), but also the distribution of shares within each category. Change of import shares within categories has mostly been confined to the two 'medium' qualities (Other Milds and Unwashed Arabicas) where ACP countries have increased their exports to Germany since enforcement of the Lome Convention in 1975. Most ACP countries in the two other categories (Columbian Milds and Robustas) have not experienced such a positive development. On the contrary, Indonesia which does not belong to this group has become one of the most important exporters of Robusta coffee to Germany during the last ten years. Quotas set by the International Coffee Agreement have favoured countries exporting unwashed coffees (with Brazil as the dominant exporter). This had especially severe effects for Germany which prefers washed coffees. Using annual data for the period 1966 to 1987 an hierarchical import allocation model is estimated where at the upper level demand for the four types of coffee is determined whereas at the lower level country-specific demand is explained. Beside the usual explanatory variables in econometric demand systems we also consider the effect of ACP membership and the influence of quota set by the International Coffee Agreement. Estimation results based on Deaton and Muellbauer's 'Almost Ideal Demand System' show that price and income reactions are quite different for the four qualities. We test the hypotheses of separability with respect to the four types of coffee and find this hypothesis to be acceptable. This allows us to estimate subsystems which determine country-specific demand for certain types of coffee. Contrary to theoretical considerations ACP membership has some influence on the countryspecific import demand structure.
Keywords: 330